Age estimation in competitive sports - Timme, M.; Steinacker, J. M.; Schmeling, A. (International Journal of Legal Medicine, 2017)
To maintain the principle of sporting fairness and to protect the health of athletes, it is essential that age limits for youth sporting competitions are complied with. Forensic scientists have developed validated procedures for age estimation in living individuals. Methods have also been published for age estimation in competitive sports. These methods make use of the ossification stage of an epiphyseal plate to draw conclusions about an athlete`s age. This article presents published work on the use of magnetic resonance imaging for age estimation in competitive sports. In addition, it looks at the effect on age estimation of factors such as an athlete`s socioeconomic status, the use of hormones and anabolic substances as well as chronic overuse of the growth plates. Finally, recommendations on the components required for a valid age estimation procedure in competitive sports are suggested.